2020
DOI: 10.1016/j.ijscr.2020.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Primary esophageal malignant melanoma successfully treated with anti-PD-1 antibody for retroperitoneal recurrence after esophagectomy: A case report

Abstract: Highlights Primary malignant melanoma of the esophagus (PMME) is a rare disease with a poor prognosis. There are few reports of treatment with the anti-programmed cell death 1 antibody, nivolumab for PMME. We report a case of retroperitoneal recurrence of PMME successfully treated with nivolumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Notably, one patient with distant LN and adrenal gland metastases received 24 months of Nivolumab as first-line therapy and succeeded in long-term survival of 34 months (Table 3 ). As other recent case studies consistently report the effectiveness of immunotherapy for metastatic PMME [ 9 , 11 ], further large scale studies are warranted to confirm the validity of immunotherapy for PMME. To date, it is unclear whether PD-L1 expression can be a predictive marker for immunotherapy response for mucosal melanoma [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Notably, one patient with distant LN and adrenal gland metastases received 24 months of Nivolumab as first-line therapy and succeeded in long-term survival of 34 months (Table 3 ). As other recent case studies consistently report the effectiveness of immunotherapy for metastatic PMME [ 9 , 11 ], further large scale studies are warranted to confirm the validity of immunotherapy for PMME. To date, it is unclear whether PD-L1 expression can be a predictive marker for immunotherapy response for mucosal melanoma [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 83%
“…In CheckMate 067 study including 79 advanced mucosal melanoma patients treated with immune checkpoint inhibitor, the five-year overall survival rate was 36% and the median overall survival was 22.7 months in the combination immunotherapy group (Nivolumab plus Ipilimumab), which was better than those of either monotherapy group [ 8 ]. For PMME, there have been only a few small-sized studies on the outcomes of immunotherapy [ 9 11 ]. In the largest study by Wang et al [ 11 ] (n = 12) patients who received programmed death (PD)-1 inhibitors for PMME showed mean progression-free survival of 15.6 months.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, one patient with distant LN and adrenal gland metastases received 24 months of Nivolumab as rst-line therapy and succeeded in long-term survival of 34 months (Table 3). As other recent case studies consistently report the effectiveness of immunotherapy for metastatic PMME [8,10], further large scale studies are warranted to con rm the validity of immunotherapy for PMME.…”
Section: Discussionmentioning
confidence: 88%
“…However, due to the extreme rarity of the disease, its clinical features are sparsely reported and treatment strategies are not standardized. Recently, treatment with immune-checkpoint inhibitor such as Pembrolizumab or Nivolumab for metastatic PMME have shown promising results [8][9][10]. However, as the number of cases were limited, more studies with consistent results are required to validate the e cacy of such treatments.In the present study, we reviewed the clinical and endoscopic features of 17 patients diagnosed with PMME in our institution and investigated their surgical and non-surgical outcomes.…”
mentioning
confidence: 99%
“…Therefore, these authors renewed the need to employ techniques such as massive gene sequencing to be able to search for biomarkers capable of predicting the response of PMME to anti-PD1 immunocheckpoint inhibitors. After another 38 cases of PMME [ 274 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 ], Endo F. et al [ 290 ] reported a case of a 70-year-old man who complained of dysphagia due to the presence of a polypoid lesion in the lower thoracic esophagus. Although the histopathological examination had provided the diagnosis of esophageal squamous carcinoma at first, with subsequent pT3N1M0 staging and clinical stage III, a histological re-evaluation after radical esophagectomy revealed the presence of atypical melanocyte cells positive for S-100 protein, Melan-A and HMB-45, and, therefore, PMME was diagnosed.…”
Section: Discussionmentioning
confidence: 99%